Mongolian “Third Neighbor Policy” and Strategic Partnership with USA (Mongolian Journal of International Affairs, 2025)
This paper examines the evolution of Mongolia–United States relations through the lens of Mongolia’s ‘Third Neighbor Policy,’ with particular attention to the influence of the United States’ Indo-Pacific Strategy. Mongolia’s security is influenced both positively and negatively depending on how the country develops its relations with its two neighbors and with highly developed nations of the East and the West, as well as how it maintains a balance among their respective interests. Mongolia faces the challenge of navigating the geopolitical dynamics between its two powerful neighbors, China and Russia, while also fostering relations with nations such as the United States and those in the European Union. This requires a delicate diplomatic strategy to ensure that no single influence dominates its foreign policy. Additionally, Mongolia must address internal pressures and economic dependencies that can arise from unequal partnerships, ensuring that its sovereignty and national interests remain protected. Therefore, studying the United States’ policy in Asia—one of the world’s major powers—and the alignment of its interests with Mongolia is essential for defining Mongolia’s policy toward the U.S. In contrast, U.S. policy toward the Asia-Pacific region has consistently included engagement with Mongolia. The terminology and concept of that regional framework were revised under President Trump’s administration, and the U.S. government’s policy toward the region was renamed the Indo-Pacific Strategy. Despite Mongolia and the United States having interacted for more than a century, diplomatic relations were established in 1987, and were elevated to the status of a “Strategic Partnership” in 2019. It is the purpose of this short article to outline the distinctive characteristics of their historical relations, the current situation, and the prospects for the future.